Early Marriage: Understanding Motivations and Impact - Khodijah Khodijah; Bagong Suyanto; IB Wirawan (MUWAZAH : jurnal kajian gender, 2024)
This research aims to explore the dominant factors of early marriage from the other perspective of married teenage girls. This Research was conducted from May 2022 until January 2023 in Singosari, Malang. Purpose sampling was used to select 20 electable informants. Data was collected directly through semi-structured interviews and analyzed using conventional content analysis methods. This research uses a qualitative method with a content analysis design for exploring topics related to cultural context. The qualitative method with content analysis design in this study uses a traditional approach. The research results showed that multiple factors encourage the decision to marry at an early age from the perspective of adolescent girls including two categories namely "socio-economic conditions" and "individual conditions." Therefore, the problem of early marriage is caused by many factors, and a multidimensional and interdisciplinary approach is needed to develop and implement systematic, effective, massive, and comprehensive steps, including programs to increase knowledge, understanding, and awareness of teenagers, parents and society about the negative impacts of early marriage. The implications of this research highlight the need for more targeted policies and interventions to prevent early marriage, as well as the important role of education and community support in changing perceptions and social norms that support this practice. This research also provides a basis for the development of youth empowerment programs that focus on improving their quality of life and well-being.